FIELD TESTS OF SPILLED SOILS - Bakhromov Makhmud Mamathanovich (Journals Park Publishing, 2023)
This article provides information on the properties of spilled soils, the amount of subsidence, self-compaction, the fact that the density of dry soil for shallower depths is higher than that of the experiment, the self-compaction characteristics of re-poured gill-like soils, as well as the field tests necessary to study the properties of spilled soils.
Keywords: Specific gravity, spilled soil, self-compaction, amount of subsidence, soil, soil density, compaction of soil, compaction technology, static or dynamic testing of soil, tests with stamps and experimental foundations.